The Uzbek Growth Puzzle - Zettelmeyer, Jeromin (IMF Working Papers; Working Paper ;, 1998)
After the break-up of the Soviet Union, Uzbekistan's output fell less than in any other former Soviet Republic, and growth turned positive in 1996/97. Given the country's hesitant and idiosyncratic approach to reforms, this record has suprised many observers. This paper first shows that a standard panel model of growth in transition systematically underpredicts Uzbek growth from 1992-1996, confirming the view that Uzbekistan's performance consitutes a puzzle. It then attempts to resolve the puzzle by appropriately extending the model. The main result is that Uzbekistan's output performance was driven by a combination of low initial industrialization, its cotton production, and its self-sufficiency in energy.